Best practice in active surveillance for men with prostate cancer: a Prostate Cancer UK consensus statement. (7th March 2019) - Merriel, Samuel W.D.; Hetherington, Liz; Seggie, Andrew; Castle, Joanna T.; Cross, William; Roobol, Monique J.; Gnanapragasam, Vincent; Moore, Caroline M.
Abstract : Objectives: To develop a consensus statement on current best practice of active surveillance (AS) in the UK, informed by patients and clinical experts. Subjects and Methods: A consensus statement was drafted on the basis of three sources of data: systematic literature search of national and international guidelines; data arising from a Freedom of Information Act request to UK urology departments regarding their current practice of AS; and survey and interview responses from men with localized prostate cancer regarding their experiences and views of AS. The Prostate Cancer UK Expert Reference Group (ERG) on AS was then convened to discuss and refine the statement. Results: Guidelines and protocols for AS varied significantly in terms of risk stratification, criteria for offering AS, and protocols for AS between and within countries. Patients and healthcare professionals identified clinical, emotional and process needs for AS to be effective. Men with prostate cancer wanted more information and psychological support at the time of discussing AS with the treating team and in the first 2 years of AS, and a named healthcare professional to discuss any questions or concerns they had. The ERG agreed 30 consensus statements regarding best practice for AS. Statements were grouped under headings: 'Inclusion/Exclusion Criteria'; 'AS follow‐up protocol' and 'When to stop AS'. Conclusion: Significant variation currently exists in the practice of AS in the UK and internationally. Men have clear views on the level of involvement in treatment decisions and support from their treating professionals when receiving AS. The Prostate Cancer UK AS ERG has developed a set of consensus statements for best practice in AS. Evidence for best practice in AS, and the use of multiparametric magnetic resonance imaging in AS, is still evolving, and further studies are needed to determine how to optimize AS outcomes.